Avaliação do papel de Nox-2 em camundongos experimentalmente infectados com Neospora caninum - Lucas, Juliana Izidoro (2023)
Neosporosis is a parasitic infection caused by Neospora caninum, an obligate intracellular protozoan belonging to the phylum Apicomplexa, which greatly impacts bovine production. The NADPH oxidases of phagocytes belong to the NOX family of multiprotein complexes that generate reactive oxygen species (ROS), which are generated in response to infection by different pathogens, through tissue inflammation and release of danger signals by the innate immune response in the stages initial infection. NOX-2, the prototype of NADPH oxidase, has been widely studied, as well as its importance in maintaining infection by different pathogens. To investigate the role of this pathway in N. caninum infection and the relationship between NOX-2 and parasitism in different tissues and periods of infection, we used mice genetically deficient for NADPH oxidase subunit 2 gp91 phox (Nox2 -/-). Expression of ROS pathway genes and parasitism in peritoneum cells, spleen, lung, liver and brain fragments were analyzed by quantitative PCR. The survival and morbidity curves were analyzed by monitoring the weight variation of the animals, in different phases of the infection, from the hyperacute phase to the chronic phase. Our results demonstrate that the ROS pathway is involved in the response to infection against N. caninum, NOX-2 was differentially expressed over the period of infection. Regarding the survival curve and the morbidity of the animals, we observed that Nox2 -/- mice had greater weight loss, in the chronic phase of the infection, from the twentieth day onwards, however this difference was not related to the parasitism of the evaluated tissues. Therefore, NOX-2 participates in the response to acute infection by N. caninum but is not related to resistance to infection according to parasitic replication in the investigated tissues.